CARBON ISOTOPE RATIOS OF PHANEROZOIC MARINE CEMENTS: RE-EVALUATING THE GLOBAL CARBON AND SULFUR SYSTEMS - Carpenter S.J.; Lohmann K.C. (My University, 1997)
Original δ13C values of abiotically precipitated marine cements from a variety of stratigraphic intervals have been used to document secular variations in the δ13C values of Phanerozoic oceans. These, together with the δ34S values of coeval marine sulfates, are used to examine the global cycling of carbon and sulfur. It is generally accepted that secular variation in δ13C and δ34S values of marine carbonates and sulfates is controlled by balanced oxidation-reduction reactions and that their long-term, steady-state variation can be predicted from the present-day isotopic fractionation ratio (ΔCΔS) the ratio of the riverine flux of sulfur and carbon (FSFC). The predicted slope of the linear relation between δ13Ccarb and δ34Ssulfate values is approximately -0.10 to -0.14. However, temporal variation observed in marine cement δ13C values and the δ34S values of coeval marine sulfates produces a highly significant linear relation (r2 = 0.80; α > 95%) with a slope of -0.24; approximately twice the predicted value. This discordance suggests that either the Phanerozoic average riverine FSFC was 1.6-3.3 times greater than today's estimates or that an additional source of 34S-depleted sulfur or 13C-enriched carbon, other than continental reservoirs, was active during the Phanerozoic. This new relation between marine δ13C and δ34S values suggests that the flux of reduced sulfur, iron, and manganese from seafloor hydrothermal systems affects oceanic O2 levels which, in turn, control the oxidation or burial of organic matter, and thus the δ13C value of marine DIC. Therefore, the sulfur system (driven by seafloor hydrothermal systems) controls the carbon system rather than organic carbon burial controlling the response of δ34S values (via formation of sedimentary pyrite).Secular variation of marine 87Sr/86Sr ratios and δ18O values argues for a coupling of δ13C and δ34S values to variation in the relative contribution of seafloor hydrothermal and continental weathering fluxes. These trends indicate that the early Paleozoic was dominated by low temperature silicate weathering, whereas the Late Paleozoic to Modern was dominated by high temperature seawater-basalt interactions. Variation in Proterozoic δ13Ccarb and δ34Ssulfate values produces a slope that is greater than that of the Phanerozoic (-0.50 vs. -0.24). This steeper slope is consistent with other geochemical data that indicate relatively high seafloor hydrothermal fluxes during the late Precambrian. We speculate that the dramatic evolutionary changes of the Neoproterozoic-Paleozoic transition occur during a waning of seafloor hydrothermal fluxes and a concomitant decrease in O2 consumption that permitted the oxygenation of seawater thought to be critical in metazoan evolution.
Keywords: Paleozoic; Proterozoic; Neoproterozoic; Precambrian; Paleozoic; Precambrian::Proterozoic; Precambrian::Proterozoic::Neoproterozoic; Precambrian; Палеозой; Докембрий::Протерозой::Неопротерозойская; Докембрий::Протерозой; Докембрий